Report of the State Board of Regents for the biennial period ending . (State of Iowa, 1956)
Contains the observations and conclusions of the Board respecting the State University of Iowa, Iowa State College of Agriculture and Mechanic Arts, Iowa State Teachers College, Iowa Braille and Sight Saving School, Iowa School for the Deaf, State Sanatorium (varies slightly)